2023
DOI: 10.1186/s13102-023-00676-6
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of adults living with HIV attending the opportunistic infections clinic at Chitungwiza central hospital in Zimbabwe towards physical activity: a cross-sectional survey

Abstract: Background Regular physical activity and exercise have been shown to be of benefit in managing the HIV disease, its complications and the side effects of HAART. The perceptions of those living with HIV toward physical activity and exercises is a key factor in advocating for participation of rehabilitation personnel in the management of this disease. However, this domain remains underexplored in Zimbabwe. Methods A descriptive cross-sectional quanti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…These individuals had either returned to regular follow-up care or had registered for the first time and took part in a one-year survey to establish a database [ 10 , 17 ]. The study population included PLWHs who met the conventional criteria for defining cases (LLPA performers) or controls (non-LLPA performers, such as MLPA and HLP performers), as well as the study’s inclusion and exclusion criteria for each comparison group [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…These individuals had either returned to regular follow-up care or had registered for the first time and took part in a one-year survey to establish a database [ 10 , 17 ]. The study population included PLWHs who met the conventional criteria for defining cases (LLPA performers) or controls (non-LLPA performers, such as MLPA and HLP performers), as well as the study’s inclusion and exclusion criteria for each comparison group [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, a case refers to a confirmed HIV + individual who took part in a previous survey and is now classified as an LLPA performer based on the study’s eligibility criteria, which were derived from prior databases [ 10 , 17 ]. The study’s criteria for defining a case included the WHO’s previous recommendation for comparison [ 9 ]. This guideline defines a case or LLPA performer as a low-intensity, low-effort activity that does not greatly elevate heart rate or cause sweating and does not meet the standards for MLPA or HLPA categories.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations